'Believe the positive' aggregation of fall risk assessment methods reduces the detection of risk of falling in older adults. (November 2020) - Menezes, Michele; Meziat-Filho, Ney Armando Mello; Lemos, Thiago; Ferreira, Arthur Sá
Highlights: Aggregating methods decays the validity of fall risk stratification. Polypharmacy outperforms aggregating up to six fall risk assessment methods. Polypharmacy or Berg Balance Scale are preferred for fall risk assessment. Abstract: Objectives: Screening programs for fall prevention in older adults may include several assessment methods. This study investigated the validity of aggregating fall risk assessment methods for stratifying the risk of falling in older adults. Methods: This secondary data analysis included 52 community-dwelling residents aged [median (interquartile range)] 74 (69–80) years. Fall occurrences were registered prospectively for six months, with 9 (17%) participants reporting at least one fall during follow-up. The fall risk assessment included the Berg Balance Scale (BBS); polypharmacy (POLY); Falls Risk Assessment Score (FRAS); Fall Risk Assessment Tool (FRAT-up); Falls Efficacy Scale (FES); and posturography with the Wii Balance Board (WBB). Aggregation of methods' results was performed according to the risk classification ('high risk' or 'low risk') assigned by their respective cut-off values under the 'believe the positive' (BP) strategy. Results: Aggregating 1 (POLY), 2 (+BBS), 3 (+FES), 4 (+FRAT-up), 5 (+FRAS), and 6 (+BBS) methods resulted in a monotonic decrease of several validity indices including (index [95% confidence interval]) diagnostic odds ratio (10.82 [2.38—54.28] to 0.59 [0.12—2.09]) and accuracy (0.67 [0.54—0.78] to 0.20 [0.11—0.31]). Conclusions: Aggregating fall risk assessment methods—BBS, POLY, FRAS, FRAT-up, FES, WBB—under the BP strategy does not increase the validity of stratification of the risk of falling in older adults.